Optimal geometry for a quartz multipurpose SPM sensor - Stirling, Julian (Beilstein Journal of Nanotechnology, 2013)
We propose a geometry for a piezoelectric SPM sensor that can be used for combined AFM/LFM/STM. The sensor utilises symmetry to provide a lateral mode without the need to excite torsional modes. The symmetry allows normal and lateral motion to be completely isolated, even when introducing large tips to tune the dynamic properties to optimal values.
Keywords: atomic force microscopy; lateral force microscopy; lateral forces; mechanical vibrations; scanning probe microscopy; scanning tunnelling microscopy

(untitled) - Tung, R. C.; Wutscher, T.; Martinez-Martin, D.; Reifenberger, R. G.; Giessibl, F.; Raman, A. (J. Appl. Phys., 2010)

(untitled) - Stirling, J.; Shaw, G. A. (Beilstein J. Nanotechnol., 2013)

(untitled) - Binnig, G.; Quate, C. F.; Gerber, C. (Phys. Rev. Lett., 1986)

(untitled) - Mate, C. M.; McClelland, G. M.; Erlandsson, R.; Chiang, S. (Phys. Rev. Lett., 1987)

(untitled) - Albrecht, T. R.; Quate, C. F. (J. Vac. Sci. Technol., A, 1988)

(untitled) - Giessibl, F. J. (Appl. Phys. Lett., 1998)

(untitled) - Torbrügge, S.; Schaff, O.; Rychen, J. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2010)

(untitled) - Giessibl, F. J.; Trafas, B. M. (Rev. Sci. Instrum., 1994)

(untitled) - Giessibl, F. J. (Appl. Phys. Lett., 2000)

(untitled) - Kawai, S.; Kitamura, S.-i.; Kobayashi, D.; Kawakatsu, H. (Appl. Phys. Lett., 2005)

(untitled) - Giessibl, F. J.; Herz, M.; Mannhart, J. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Szlufarska, I.; Chandross, M.; Carpick, R. W. (J. Phys. D: Appl. Phys., 2008)

(untitled) - Giessibl, F. J.; Bielefeldt, H.; Hembacher, S.; Mannhart, J. (Appl. Surf. Sci., 1999)

(untitled) - Giessibl, F. J. (Phys. Rev. B, 1997)

(untitled) - Giessibl, F. J.; Pielmeier, F.; Eguchi, T.; An, T.; Hasegawa, Y. (Phys. Rev. B, 2011)

(untitled) - Gross, L.; Mohn, F.; Moll, N.; Liljeroth, P.; Meyer, G. (Science, 2009)

(untitled) - van Vörden, D.; Lange, M.; Schmuck, M.; Schmidt, N.; Möller, R. (Beilstein J. Nanotechnol., 2012)

(untitled) - Berger, J.; Švec, M.; Müller, M.; Ledinský, M.; Fejfar, A.; Jelínek, P.; Majzik, Z. (Beilstein J. Nanotechnol., 2013)

Mechanics of Materials - Gere, J. M.; Goodno, B. J. (Cengage Learning, 2012)

(untitled) - Lozano, J. R.; Kiracofe, D.; Melcher, J.; Garcia, R.; Raman, A. (Nanotechnology, 2010)

(untitled) - Heyde, M.; Kulawik, M.; Rust, H.-P.; Freund, H.-J. (Rev. Sci. Instrum., 2004)

NaugaNeedles
Private Communication.

(untitled) - Majzik, Z.; Setvín, M.; Bettac, A.; Feltz, A.; Cháb, V.; Jelínek, P. (Beilstein J. Nanotechnol., 2012)